Kemampuan Guru dalam Mengajar Aktivitas Musik di TK - Hesti Putri Setianingsih; Endah Tri Wahyuningsih; Nur Eka Wahyuningsih Riyadi (Universitas Tadulako, 2022)
This study aims to explore the teacher's role in the use of music and identify the types of music learning applied in kindergarten in stimulating the development of early childhood music. Teachers in kindergartens (N=100) in the kindergarten area of ​​Palu City were asked for data to fill out online questionnaires via google form. Most teachers stated that the use of music is always done every day, especially singing learning activities, listening to children's songs played through cassettes and movement and song learning activities. Teachers also use music to build children's enthusiasm, distract children when children get bored in class, and involve children in all their activities using music to connect the themes that will be studied at that time. Teachers consider music to be the most important and dominant thing in early childhood learning, because it contributes a lot to children's learning and brain development. However, the current obstacle, according to him, is because of the limited ability of teachers in music and there has been no training on the importance of learning music in early childhood, so it is believed that currently teachers are limited in providing music lessons in kindergarten. Therefore, the implementation of teacher preparation and teacher training to learn music in early childhood needs to be socialized.